An initial boundary value problem for the Boussinesq equation in a Trapezoid - M.T. Jenaliyev; A.S. Kassymbekova; M.G. Yergaliyev; A.A. Assetov (Қарағанды университетінің хабаршысы. Математика сериясы, 2022)
This paper considers an initial boundary value problem for a one-dimensional Boussinesq-type equation in a domain, that is, a trapezoid. Using the methods of the theory of monotone operators, we establish theorems on their unique weak solvability in Sobolev classes.